Perspectivas teóricas contemporáneas de la educomunicación y la comunicación/desarrollo en América Latina - Silva Argoti, Alejandra Pamela (2013)
The hurriedly advance of communication, specially the technological area, has become a transcendental phenomenon in a scientifical-technological-educational-communicative revolution, where lies the foundations of the post-industrial society that has been characterized for being a communication of information and technology, moreover, it describes countries with a delayed industrial growth as having a inefficient systematical and communication methods due to its inadequate use. In the communication society, technology, commonly used as an instrument to control nature, has become a mediating entity for information growth and construction of the world as image.